Recent Advances in Gold Nanorods‐Based Cancer Theranostics. Issue 12 (6th August 2021) - Rizwan Younis, Muhammad; He, Gang; Gurram, Bhaskar; Lin, Jing; Huang, Peng
Abstract : Gold nanorods (GNRs) with a unique localized surface plasmon resonance (LSPR) property have shown groundbreaking performance in catalysis, sensing, and biomedical applications. Intrinsic inertness, biocompatibility, a tunable longitudinal LSPR band in the near‐infrared (NIR)‐I/II region, high extinction coefficient, and remarkable optical properties all make GNRs excellent photothermal (PT) nanoagents, photosensitizers, and imaging contrast agents for drug delivery, cancer phototherapy, and multimodal imaging‐guided cancer therapy. In this periodic update, bottom–up fabrication of long and short GNRs by seed‐mediated and seedless methods is reviewed, with elaboration concerning the tuning of LSPR band and the generation of localized hyperthermia via light to heat conversion. Recent advances in applications of GNR research in bioimaging, therapy, and theranostics of cancer are then reviewed. Unmet challenges and critical points are discussed with focus given to translation from bench to clinic. Abstract : Gold nanorods (GNRs), 1D plasmonic material, possess tunable localized surface plasmon band, excellent photostability, high absorption cross section, and extinction coefficient. These fascinating physiochemical features endow GNRs with promising biomedical potential for efficient tumor diagnosis through PT/photoacoustic imaging, reactive oxygen species/thermal ablation‐mediated antitumor photodynamic/PT therapy, and simultaneous tumor diagnosis and treatment.